Analysis of the monitoring status of residual nitrite in meat products in China from 2000 to 2011. (February 2018) - Zhang, Hongchao; Sun, Changbao; Han, Wanjun; Zhang, Jiaxiu; Hou, Juncai
Abstract: The aim of this article was to analyze the monitoring status of nitrite in meat products consumed from 2000 to 2011 in 24 provinces, autonomous regions or direct-controlled municipalities in China. Statistical analyses were performed on the monitoring status including number, proportion, and distribution of 13, 316 samples, of which 11, 320 (85%) contained up to 2808.2 mg/kg nitrite and 1996 (15%) contained no nitrite. A total of 10, 299 samples (77%) qualified for GB/T 5009.33-2003, 2003; however, 3017 samples (23%) contained nitrite at levels higher than the national standard. The districts with high percentage of samples with no nitrite were Shanghai (49%), Beijing (47%), and Liaoning (30%). While the districts with high percentage of meat products containing nitrite at levels exceeding the national standard were Jiangxi (49%), Jiangsu (33%), Shandong (29%) and Sichuan (29%). Therefore, the status of residue nitrite in meat products is of concern. Highlights: The monitoring status of nitrite in meat products consumed in China was analyzed. 13, 316 samples with nitrite levels ranging from 0 to 2808.2 mg/kg were determined. In China, nitrite is widely present in meat products. Long-term practices for the supervision of nitrite in food should be strengthened.